Evaluation of the Effects of systemic Therapy on Inflammatory Markers and Disease Severity in Patients With Pemphigus - Mehmet Enes Güner; Perihan Ozturk; Mine müjde Kuş (Dermatology Practical & Conceptual)
Introduction: In recent years, various inflammatory markers that can change in inflammatory states have been investigated. On the basis of these, we thought that inflammatory markers could also be used in the treatment of pemphigus disease and monitoring its activity.